Byzantine amphoras from the Roman fort of Apsaros (modern Gonio, Georgia) - Komar, Paulina; Rogava, Andria; Motskobili, Tatuli (Rei Cretariae Romanae Fautorum Acta, 2024)
This paper presents the first study of Byzantine amphoras that were discovered by the Gonio–Apsaros Polish–Georgian Expedition at the Roman fort of Apsaros (modern Gonio, Georgia). Seasons 2018, 2019 and 2020 were particularly rich in Byzantine material as they provided 315 diagnostic fragments of both locally produced and imported transport containers, dated to the late 6th and 7th centuries AD, which form the basis of this study. Pontic imitations of LRA1 (Antonova 5) were the most common amphoras in Apsaros, with Colchian Ch ID form holding the second post. Containers from Sinope and Heracleia Pontica also reached the fortress in significant numbers; contrary, products from the northern or western Black Sea region were hardly attested. Imports outside of the Pontic area appeared in very low quantities, which points to a regionalization of trade and predominance of the local supply of Apsaros during this period.